2007
DOI: 10.1098/rstb.2007.2197
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow hydrology in the boreal region under the influences of climate and human interference

Abstract: The boreal region has a subarctic climate that is subject to considerable inter-annual variability and is prone to impacts of future warming. Climate influences the seasonal streamflow regime which typically exhibits winter low flow, terminated by spring freshet, followed by summer flow recession. The effects of climatic variation on streamflow cannot be isolated with confidence but the impact of human regulation of rivers can greatly alter the natural flow rhythm, changing the timing of flow to suit human dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 28 publications
5
81
0
Order By: Relevance
“…Projections of future changes in Rocky Mountain rivers suggest that the predicted summer flows in 2005-2055 may decline considerably, while winter and early spring flows may increase, resulting in ∼ 3-9 % decline in the annual discharge (Shepherd et al, 2010). Generally under warming scenarios, winter flows will increase, the spring freshet dates will advance, but peak flows will decline (Woo et al, 2008). Climatic changes, land cover/use changes, and enhanced water extractions for various societal and commercial needs including the oil sands development near Fort McMurray, which is projected to increase by 200 % by 2015 (Pavelsky andSmith, 2008), may continue to decrease Lake Athabasca inflow rates.…”
Section: Potential Implications To Water Levels Of Lake Athabascamentioning
confidence: 99%
See 2 more Smart Citations
“…Projections of future changes in Rocky Mountain rivers suggest that the predicted summer flows in 2005-2055 may decline considerably, while winter and early spring flows may increase, resulting in ∼ 3-9 % decline in the annual discharge (Shepherd et al, 2010). Generally under warming scenarios, winter flows will increase, the spring freshet dates will advance, but peak flows will decline (Woo et al, 2008). Climatic changes, land cover/use changes, and enhanced water extractions for various societal and commercial needs including the oil sands development near Fort McMurray, which is projected to increase by 200 % by 2015 (Pavelsky andSmith, 2008), may continue to decrease Lake Athabasca inflow rates.…”
Section: Potential Implications To Water Levels Of Lake Athabascamentioning
confidence: 99%
“…The analyses over 1977-2010 are mainly conducted on the observed data, which are more reliable and avoid the uncertainty inserted in the reconstruction of the time series for gauges on the smaller rivers. The highlands of the Athabasca River (e.g., near Jasper) are fed both with abundant snowmelt and seasonal glacier ablation from high elevations of the Rocky Mountains, which intensifies in the summer and results in high flows then (Woo and Thorne, 2003). Projections of future changes in Rocky Mountain rivers suggest that the predicted summer flows in 2005-2055 may decline considerably, while winter and early spring flows may increase, resulting in ∼ 3-9 % decline in the annual discharge (Shepherd et al, 2010).…”
Section: Potential Implications To Water Levels Of Lake Athabascamentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined how lake ice might respond to changes in both temperature and precipitation, and sensitivity analysis has shown that ice phenology is most sensitive to changes in air temperatures while ice thickness is more sensitive to snow cover (e.g., Vavrus et al, 1996;Duguay et al, 2003;Gao and Stefan, 2004;Williams et al, 2004;Morris et al, 2005) (see Brown and Duguay, 2010 for a detailed comparison). While most work involving ice cover changes has been done for specific locations, Walsh et al (1998) produced gridded ice phenology for the entire Northern Hemisphere using historical mean climate data to create the first wide-scale examination of lake ice phenology.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers advocate selecting only those gauging stations with a drainage area within a defined size range to avoid unique responses being masked by larger catchment areas, or for other reasons (Woo et al 2006, Stahl et al 2010. However, applying restrictions on the catchment size can result in a considerable reduction in the number of available gauging stations for a RHN.…”
Section: Common Network Issuesmentioning
confidence: 99%